Lethargy and quadraparesis as initial manifestations of covid-19 child: Case report. (December 2022) - Hammed, Ali; Badour, Maysaa; Baqla, Sameer
Abstract: Introduction: and importance: SARS-CoV-2 infection classically presents with fever and respiratory illness. However, neurological manifestations are also being reported in the literature. Transverse myelitis is caused by inflammation of spinal cord. There are various possible etiologies for this neurologic condition that include viral or bacterial infections. Case presentation: We present a case of 2 –year-old female complained of weakness of all four limbs and lethargy.She was febrile(39), respiratory rate 30/min and oxygensaturation of 89% on room air. Neurological examination revealed intact cranial nerves, GCS of 14/15 and upper and lower limbs weakness with medical research council(MRC) score of 2/5 Sensory examination showed decreased sensation of all modalities in lower limbs with a sensory level at T4. Clinical discussion: Laboratory results and cerebrospinal fluid (CSF) analysis showed normal values. Brain MRI was normal. An urgent Gadolinium-enhanced magnetic resonance imaging of the whole spine was done and revealed extensive diffuse hyper intense signal involving predominantly the grey matter of the upper cervical spinal cord. Mild enlargement and swelling of the cervical cord were also note. She was given pulse doses of IV methylprednisolone 30mg/kg followed by oral prednisolone for 40 days. She was also given IV gamma globulin 400mg/kg for five days. A marked improvement of his neurological deficit was noted over a period of 16 days after treatment. Conclusion: when a patient with myelopathy is systemically ill with fever andloss of consciousness, prompt investigation of the causative agent is needed for appropriate management. Even after the pandemic Status; COVID-19 should be considered a differential diagnosis in patients presenting with loss of consciousness, ataxia, convulsions, motor deficits, encephalitis, myelitis, or neuritis. Highlights: acute myelitis as a neurological complication of COVID-19 infection SARS-CoV-2 infection classically presents with fever and respiratory illness. When transverse myelitis is a result of viral or bacterial infection, it is usually considered as an immune mediated response.